Muslim Customer Loyalty in Buying Decisions for Halal Fashion Products - Mona Inayah Pratiwi (Politeknik Negeri Semarang, 2023)
This study aims to analyze the effect of product and design, reputation and brand value on purchasing decisions for halal fashion products. In addition, this study also analyzes the moderating effect of customer loyalty that influences the product and design, reputation and brand value on purchasing decisions for halal fashion products. This research is a survey research with a quantitative approach through a questionnaire instrument that was distributed to 100 Muslim customer respondents in Semarang Regency. Data analysis techniques used in this study are multiple linear regression tests and moderating regression analysis (MRA) tests. The results of the study show that product and design, reputation and brand have a positive and significant effect on purchasing decisions for halal fashion products. Meanwhile, moderating customer loyalty does not moderate (weaken) the influence of products and designs on purchasing decisions for halal fashion products. Customer loyalty also does not moderate the influence of reputation and brand on purchasing decisions for halal fashion products.